The Textual Construction of High Needs for Funding Special Education in Ontario - Daniel, Yvette (Canadian Journal of Education/Revue canadienne de l’éducation, 2005)
In this article I have examined one particular funding policy for special education in Ontario. Specifically, I was concerned with the deleterious effects of the interpretations and implementations of this policy. To make claims to fund special needs, school boards had to implement a highly impersonal bureaucratic process that separated the textual mode from the lived reality. The all‐consuming process of identification and labeling of students guided by stringent Ministry‐imposed criteria led to unwanted and unintended consequences. Key words: education policy, funding, accountability, institutional ethnography, special education, Ontario education Dans cet article, l’auteure analyse une politique de financement ayant trait à l’orthopédagogie en Ontario. Elle se préoccupe tout particulièrement des effets délétères des interprétations et des applications de cette politique. Les commissions scolaires qui voulaient demander des fonds pour soutenir l’intervention orthopédagogique ont dû mettre sur pied un processus bureaucratique très impersonnel qui séparait l’aspect formel de l’intervention de la réalité vécue. Le processus fastidieux d’identification des élèves qualifiés d’« élèves en difficulté » à l’aide des critères stricts imposés par le ministère a entraîné des conséquences indésirables. Mots clés : politique en matière d’éducation, financement, imputabilité, ethnographie institutionnelle, orthopédagogie, éducation en Ontario.